Kajian Dinamika Perkebunan Sawit di Propinsi Kalimantan Timur - Zuhdi Yahya; Akas Pinaringan Sujalu (Jurnal Penelitian Pendidikan IPA, 2025)
Oil palm plantations, can be utilised as part of agroforestry systems to mitigate some of the negative impacts of deforestation in East Kalimantan. This research was conducted through a desk-based study and field assessment to explore how these expectations play out in the palm oil sector in East Kalimantan. Research find that oil palm plantation poses serious deforestation challenges to the concept of green growth, as 44% of land allocated for plantations is still forested. At the same time, there may be opportunities to avoid deforestation and pursue more sustainable oil palm development pathways, as 87% of concessions have yet to be planted, however it has yet to be seen whether the political will exists to pursue this shift in policy. However, the conversion of forests to oil palm plantations, including those implemented as agroforestry systems, still poses ecological and social challenges. The development of oil palm plantations is supported by several government regulations, although their implementation in the regions creates various obstacles.